2019
DOI: 10.3390/genes10120971
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrial Microbiota at Term of Normal Pregnancies

Abstract: The endometrium is a challenging site for metagenomic analysis due to difficulties in obtaining uncontaminated samples and the limited abundance of the bacterial population. Indeed, solid correlations between endometrial physio-pathologic conditions and bacteria compositions have not yet been firmly established. Nevertheless, the study of the endometrial microbiota is of great interest due to the close correlations between microbiota profiles, women’s health, and successful pregnancies. In this study, we decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…ddPCR (Bio-Rad, Hercules, CA, USA) was performed to determine the total number of 16S copies by using universal primers targeting the V5–V6 regions of 16S rDNA [31], as they have been used successfully in other DNA metabarcoding analyses (primer sequences: forward, B-V5 : 5′-ATTAGATACCCYGGTAGTCC-3′; reverse, A-V6, 5′-ACGAGCTGACGACARCCATG-3′) [32, 33]. For the quantification of the gene copy numbers for Akkermansia muciniphila 16S rRNA, specific primers targeting the V7–V8 regions were used (primer sequence: forward, AM1 : 5′-CAGCACGTGAAGGTGGGGAC-3′; reverse, AM2 : 5′-CCTTGCGGTTGGCTTCAGAT-3′) [34].…”
Section: Methodsmentioning
confidence: 99%
“…ddPCR (Bio-Rad, Hercules, CA, USA) was performed to determine the total number of 16S copies by using universal primers targeting the V5–V6 regions of 16S rDNA [31], as they have been used successfully in other DNA metabarcoding analyses (primer sequences: forward, B-V5 : 5′-ATTAGATACCCYGGTAGTCC-3′; reverse, A-V6, 5′-ACGAGCTGACGACARCCATG-3′) [32, 33]. For the quantification of the gene copy numbers for Akkermansia muciniphila 16S rRNA, specific primers targeting the V7–V8 regions were used (primer sequence: forward, AM1 : 5′-CAGCACGTGAAGGTGGGGAC-3′; reverse, AM2 : 5′-CCTTGCGGTTGGCTTCAGAT-3′) [34].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated that asymptomatic women harbour commensal microbial communities in their uterus [8,11,16,22,102], and that the uterine microbiome seems to be altered in women who suffer gynaecological pathologies such CE [14][15][16], endometriosis [17,19,20], dysfunctional endometrial bleeding [22], endometrial polyps [16], endometrial cancer or hyperplasia [16,[23][24][25], and infertility [4,8,11,13] (Table 1). All these studies support the evidence that the uterine microbial composition is clinically relevant and requires further investigation.…”
Section: Uterine/endometrial Microbial Composition In Health and Diseasementioning
confidence: 99%
“…Acinetobacter [102,103], Bacillus [103], Barnesiella [23], Bifidobacterium [11], Blautia [23], Corynebacterium [102], Desulfosporosinus [16], Enterobacter [16], Escherichia [102,103], Fusobacterium [22], Gardnerella [11], Jonquetella [22], Lactobacillus [8,11,16,19], Parabacteroides [23], Prevotella [11,22], Propionibacterium [102], Pseudomonas [16], Ralstonia [16], Shigella [23], Staphylococcus [23,102], Streptococcus [11,102] Infertility…”
Section: Healthymentioning
confidence: 99%
“…In contrast, it was detected in only 1/22 (4.5%) background technical controls. Acinetobacter has been reported in prior sequence-based investigations of the human endometrium (20, 23, 24, 29, 30), and it has been cultured from the human endometrium as well (95). The primary ASV classified as Ottawia was detected in 6/10 (60%) uterine wall samples at an average relative abundance of 10.5%.…”
Section: Discussionmentioning
confidence: 99%